Keberdayaan Masyarakat Putus Sekolah di Era Ekonomi Kreatif Berbasis Pemberdayaan Masyarakat - Syaifudin Syaifudin (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2021)
The uncertainty of economic conditions during the Covid-19 pandemic requires humans to survive in all limitations. However, the world of schools is considered to be able to improve the quality of human resources, on the contrary, it is increasingly difficult to access by the community, especially the lower class community. It is proven that every year the dropout rate always increases. Therefore, in order to provide social capital to these out-of-school children, job skills training is needed. With this job skills training, at least the children who drop out of school have the capital to apply for jobs or become entrepreneurs. One of the areas that is part of the children who drop out of school is the RT area. 006, RW. 014 Cengkareng Barat Village, West Jakarta. Because almost 20% of teenagers in this area have dropped out of school, both from elementary, junior high, and high school. Some even don't go to school at all. So it is not surprising that many youths in this region are unemployed. Therefore, in order to minimize the unemployment rate in this region, it is necessary to provide a skill set for these teenagers who drop out of school. So that later they have additional skill capital to apply for jobs or even become their own entrepreneurs. ABSTRAK Ketidakpastian kondisi ekonomi di masa pandemi Covid-19 menuntut manusia bertahan dalam segala keterbatasan. Akan tetapi dunia sekolah yang di anggap dapat meningkatkan kualitas sumber daya manusia, justru sebaliknya makin sulit di akses oleh masyarakat, khususnya masyarakat kecil kebawah. Terbukti tiap tahunnya angka putus sekolah selalu mengalami kenaikan. Oleh karena itu guna memberikan modal sosial kepada anak yang putus sekolah ini, maka diperlukan pelatihan ketrampilan kerja. Dengan pelatihan ketrampilan kerja ini, setidaknya anak yang putus sekolah itu memiliki modal untuk melamar pekerjaan atau berwirausaha. Salah satu wilayah yang termasuk bagian dari anak yang putus sekolah ini yaitu wilayah RT. 006, RW. 014 Kelurahan Cengkareng Barat, Jakarta Barat. Karena hampir 20% remaja di wilayah ini mengalami putus sekolah, baik dari SD, SMP, maupun SMA. Bahkan ada yang sama sekali tidak sekolah. Maka tidak heran banyak remaja di wilayah ini yang menganggur. Oleh sebab itu untuk meminimalisir tingkat pengangguran di wilayah ini, maka diperlukan sebuah pembekalan ketrampilan bagi para remaja yang putus sekolah ini. Agar nantinya mereka memiliki modal ketrampilan tambahan untuk melamar pekerjaan atau bahkan berwirausaha sendiri.